ANALISIS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PRODUK PANGAN BEKU PERSPEKTIF EKONOMI ISLAM DI DC FROZEN FOOD ROGOJAMPI BANYUWANGI - Faiqotul Hima; Abdul Majid; Luckman Ashary; Mohammad Saleh (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2023)
This research was conducted to answer the formulation of the problem: (1) How is the Analysis of Service Quality and Price in Achieving Consumer Satisfaction in Purchasing Frozen Food Products at DC Frozen Food.id Rogojampi Banyuwangi? (2) What is the review of the Islamic Economic Perspective on Service Quality and Price in Achieving Consumer Satisfaction in Purchasing Frozen Food Products at DC Frozen Food.id Rogojampi Banyuwangi? The method used in this research is qualitative research with descriptive research type. Data collection techniques used are interviews, observation, and documentation related to the formulation of the problem. The first conclusion, service determines consumer satisfaction. They are very happy when these employees are always friendly and responsive when consumers come who want to shop and buy frozen food products. Meanwhile, on the other hand, price is very decisive, because frozen food products tend to have affordable prices and according to their quality and benefits. Second, viewed from the perspective of Islamic Economics that is service quality, Islam views that DC Frozen Food.id Rogojampi in running its business has provided good service and is in accordance with the principles of Islamic Economics which is based on the Qur'an and hadith. And the price set by DC Frozen Food.id Rogojampi is in accordance with the concept of Islamic economics, namely the principle of justice. Like and like from both parties or willingness and there is no coercion and no one is harmed from both parties (dzolim). Meanwhile, setting prices is in accordance with the concept of Islamic economics.